Roteiro eureka: dissipando a névoa da interdisciplinaridade entre professores de ciências na natureza no ensino fundamental – anos finais - Wagner, Marluce Tuparaí (2023)
Interdisciplinarity has been requested in the teaching and learning process because scientific knowledge and human reality are complex. Therefore, strictly disciplinary approaches denote a fragmented teaching. In view of this, this study linked to the Graduate Program in Science Education – Unipampa/Uruguaiana proposes to present a script for planning interdisciplinary activities implemented in a Training Workshop for a group of 24 teachers belonging to the Municipal network of Uruguaiana/RS. In this perspective, the objective was to elaborate and investigate whether the planning script constructed, in this research, favors the interdisciplinary practice of Natural Sciences teachers in Elementary School - Final Years, based on a Pedagogical Intervention, a qualitative and descriptive approach and exploratory. Teacher training took place with three face-to-face meetings and one asynchronous remote meeting. The main activity was Eureka: script for planning interdisciplinary activities. Five data collection instruments were used (preliminary questionnaire, participant observation, initial questioning, scripts filled out by the teachers and a final critical reflection on the script) in order to triangulate data collection. Data were analyzed using thematic analysis and intervention evaluation, based on findings related to the effects of the intervention on participants and findings related to the implementation of the script. It stands out as results of this research that the researched teachers have fragile understandings about interdisciplinarity that, combined with initial and continued training without emphasis on interdisciplinarity, make interdisciplinary actions in the classroom unfeasible. Regarding the Eureka Roadmap, this was considered as a potential planning tool for those who have greater contact with interdisciplinary references. In addition, it is noteworthy, as a general analysis, that eight general contexts were found that point to potentialities or limitations for interdisciplinary work. They are characteristics of interdisciplinary teaching and the perceptions of professors and students about interdisciplinarity; the precariousness of tools, strategies, methodologies and implementation examples; the need for continuing education on the subject; initial training with an interdisciplinary perspective; few interdisciplinary practices implemented in schools and little dissemination of interdisciplinary practices; in addition to reduced interdisciplinary planning time and limited resources with regard to infrastructure, materials and technology. The results point to the urgency of further work and practical research on interdisciplinarity in order to fill the gaps described.